1998
DOI: 10.1021/jp980921k
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Distribution at the Semiconductor/Solution Interface

Abstract: In semiconductor electrochemistry there is considerable confusion concerning the potential distribution at the semiconductor/solution interface under weak depletion and accumulation conditions. The applied potential is partitioned between the space charge layer in the semiconductor and the Helmholtz layer on the solution side of the interface. Under deep depletion conditions, a change in the applied potential usually appears across the space charge layer and the band bending can be determined using the Mott-Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 75 publications
0
47
0
1
Order By: Relevance
“…Searson and coworkers [43] have shown that the seeming cathodic Tafel slope could be modified by the structure of the interface. These authors have used an equivalent electrical circuit to describe the sharing of voltage drops between the space charge layer and the Helmholtz layer.…”
Section: Evaluation Of the Rest Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Searson and coworkers [43] have shown that the seeming cathodic Tafel slope could be modified by the structure of the interface. These authors have used an equivalent electrical circuit to describe the sharing of voltage drops between the space charge layer and the Helmholtz layer.…”
Section: Evaluation Of the Rest Potentialmentioning
confidence: 99%
“…32), but V pzc 0 were equal to V fb . The shift between V fb and V pzc 0 has been emphasized [43,56] to occur when the space charge layer capacitance is too high and not negligible in front of 0 . This was actually the case for magnetite bur not for the slightly reduced maghemite for which the value of the space charge layer capacitance was about 30 times lower than the one for magnetite (cf.…”
Section: Influence Of the Inner Potential Of Zero Chargementioning
confidence: 99%
“…If the reference electrode exhibits constant potential independent of the solution composition, changes in E as a function of pH, ionic strength, electrolyte composition, and adsorbate concentration arise from reactions at the mineral/solution interface. Multiple planes of charge can be specified that dictate the total potential drop across this interface, including the space charge layer in the mineral surface, the Helmholtz layer, and the diffuse layer in solution (as opposed to just the latter two for insulators) (Garrett and Brattain, 1955;Morrison, 1980;Natarajan et al, 1998). As will be discussed below, for conditions where the voltage drops across two of the three layers are understood, the third can be directly determined.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is known for H-terminated Si and the values for higher doped samples have been calculated taking into account the deviation from the Boltzmann approximation for very high doped samples (using the FermiDirac integral values). For the determination of the respective potential drop in the space charge layer, V SC , we use the expression [42]: (8) and Table I shows the evaluation. The left four columns give doping level, onset potential for the current, the flatband potential and the difference V on -V fb .…”
Section: Doping Dependence Of Electron Injection Into Si(111)mentioning
confidence: 99%